Investigating The Influence of Social Media Influencers on Consumer Decision Making Process of Plurals and Millennials - Sidhu, Lovedeep Singh; Saini, Ramandeep (Gyan Management Journal, 2021)
Objective: The study examines how consumer decision making process of millennials and plurals gets impacted due to social media influencers. The impact was measured by using social media influencers as exogenous construct and five stages of consumer decision making process as endogenous construct.Research Methodology: A theoretical model was developed by reviewing earlier literature available on different journals and websites. A sample of total 500 respondents was collected through structured questionnaire by using stratified proportionate sampling whereby count of plurals and millennials was 250 each. The data was examined through Smart PLS 3.0 by performing structure equational modelling. Findings: The results indicated that all the stages of consumer decision making process of millennials and plurals were impacted due to social media influencers. Furthermore, the highest impact was found on need recognition stage (H1), followed by post purchase behaviour (H5), purchase stage (H4), evaluation of alternatives (H3), and search of information (H2).Limitations: This research has few limitations as it was conducted in only northern states of India; however, further research can be conducted in other areas which may yield other productive results. Moreover, only behavioural aspect of consumer attitude was tested, rather cognitive and affective components of consumer behaviour can be considered in future research.Implications: Through this research, marketers can avail the opportunity to understand buying process of two generations: plurals and millennials which would be valuable for firms in strategizing digital marketing plans and policies to target both age groups on social media. This study has illustrated buying process of two generations in order to fulfil the literature gap as there was inadequate literature on plurals and millennials. Hence, both literature gap and originality have been attained and fulfilled.